2021
DOI: 10.3390/nu13072151
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Product Intake and Long-Term Risk for Frailty among French Elderly Community Dwellers

Abstract: Dairy products (DP) are part of a food group that may contribute to the prevention of physical frailty. We aimed to investigate DP exposure, including total DP, milk, fresh DP and cheese, and their cross-sectional and prospective associations with physical frailty in community-dwelling older adults. The cross-sectional analysis was carried out on 1490 participants from the Three-City Bordeaux cohort. The 10-year frailty risk was examined in 823 initially non-frail participants. A food frequency questionnaire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This study revealed that the intake of animal proteins (fish, meat, and egg) was significantly high in the HI group. Adequate energy intake, especially proteins, was reported to be important in preventing frailty [ 11 , 27 ]. Previous studies have revealed the relationship between the number of remaining teeth and nutritional status [ 28 , 29 ] and between masticatory function and nutritional status [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed that the intake of animal proteins (fish, meat, and egg) was significantly high in the HI group. Adequate energy intake, especially proteins, was reported to be important in preventing frailty [ 11 , 27 ]. Previous studies have revealed the relationship between the number of remaining teeth and nutritional status [ 28 , 29 ] and between masticatory function and nutritional status [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the traditional MeDi, milk and dairy products are considered as detrimental food components, whereas in the LMD they are regarded otherwise. Nevertheless, a recent analysis of the 3C-Study-Bordeaux did not observe any significant associations between total dairy products and their sub-types (milk, fresh dairy products, and cheese) and frailty prevalence and risk [ 65 ]. These results should be interpreted with caution as their generalizability to the Lebanese population and the LMD is limited since the type of fresh dairy products and cheese consumed in Lebanon is completely different than that consumed by the French population.…”
Section: Discussionmentioning
confidence: 99%